Subterahertz chaos generation by coupling a superlattice to a linear resonator - Hramov, A.E.; Makarov, V.V.; Koronovskii, A.A.; Kurkin, S.A.; Gaifullin, M.B.; Alexeeva, N.V.; Alekseev, K.N.; Greenaway, Mark Thomas; Fromhold, Timothy Mark; Patanè, Amalia; Kusmartsev, F.V.; Maksimenko, V.A.; et al. (American Physical Society, 2014)
We investigate the effects of a linear resonator on the high-frequency dynamics of electrons in devices exhibiting negative differential conductance. We show that the resonator strongly affects both the dc and ac transport characteristics of the device, inducing quasiperiodic and high-frequency chaotic current oscillations. The theoretical findings are confirmed by experimental measurements of a GaAs=AlAs miniband semiconductor superlattice coupled to a linear microstrip resonator. Our results are applicable to other active solid state devices and provide a generic approach for developing modern chaos-based high-frequency technologies including broadband chaotic wireless communication and superfast random-number generation.